AB1007 Increased Vascular Wall Inflammation in Patients with Active Rheumatoid Arthritis as Measured by an 18F-Fdg-Pet/Ct Scan. (10th June 2014) - Agca, R.; Sijl, A.M.; Smulders, Y.M.; Voskuyl, A.E.; van der Laken, C.; Boellaard, R.; Lensen, K.D.; Nurmohamed, M.T.
Abstract : Background: Patients with rheumatoid arthritis (RA) have an elevated risk of developing cardiovascular disease (CVD). Like active RA, atherosclerosis is an inflammatory process. There are indications that aortic inflammation in atherosclerosis can be detected on 18 F-Fluorodeoxyglucose-positron emission tomography/computed tomography ( 18 F-FDG-PET/CT). Objectives: To quantify 18 F-FDG uptake in large arteries of RA patients using PET/CT, as potential reflection of vascular wall inflammation in areas of atherosclerosis, and its association with disease activity in patients with RA as compared to controls. Methods: 18 F-FDG-PET/CT was performed in patients with active RA (DAS28 >4.0; n=29) and in controls with osteoarthritis (OA; n=11). Semi-quantitative FDG-uptake was determined by calculation of the mean standardized uptake value (SUV) and tissue-to-background ratio (TBR) using 18 F-FDG activity in the vena cava as background. One volume of interest (VOI) of an arterial segment with maximum 18 F-FDG uptake was used for SUV calculation (focal arterial uptake). Total arterial uptake was estimated by using the mean of all focal arterial uptakes in all arteries. Results: Focal as well as total arterial uptake of 18 F-FDG was the highest in patients with RA. SUV was significantly higher in RA for the thoracic aortic tract, the abdominal aorta and the femoral arteries as compared to OA controls. CRP was associated with an increased total arterial uptake as well as an increased focal arterial uptake in the thoracic aortic tract, the abdominal aorta, the iliac arteries and the femoral arteries. DAS28 >2, 6 was also correlated with total arterial uptake and uptake in the thoracic aortic tract, the abdominal aorta and the iliac arteries. There were no significant differences in TBR between RA and OA. Conclusions: Increased focal vascular wall uptake of 18 F-FDG as sign of vascular inflammation was found in several arterial segments of RA patients. CRP and clinical RA activity were correlated with 18 F-FDG uptake in most of these arteries. Overall, total arterial uptake was higher in RA patients and it was correlated with CRP and disease activity. The lack of differences in TBR measurements requires further study. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4185